Architect of corporate responsibility : The story of Alice Tepper Marlin and the founding of Social Accountability International - Marlin, Alice T. (Social entreprenurship series)
"In this program Alice offers compelling insights, strategies and a personal stories from some the innovative, high impact social entrepreneurship".